ANALISIS KEDISIPLINANAN BELAJAR SISWA KELAS TINGGI DI SD NEGERI 37 PEKANBARU - Safitri, Celia; Munjiatun; Noviana, Eddy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates learning discipline among upper-grade elementary students at SD Negeri 37 Pekanbaru and tests whether discipline differs by gender and parents’ occupation. A cross-sectional quantitative survey was administered to 166 Grade 4–5 students (academic year 2025/2026) selected through random sampling. Learning discipline was measured using a Likert-type questionnaire covering four dimensions: compliance with school rules, compliance with learning activities at school, compliance in completing assignments, and compliance with learning activities at home; teacher interviews were used as supporting information. Data were analyzed using descriptive statistics, an independent-samples t-test, and one-way ANOVA. Overall, students’ learning discipline was predominantly in the high category (M = 87.64); the highest dimension was compliance with school rules, whereas compliance with learning activities at school was comparatively lower. No statistically significant differences were found by gender (p = .061) or parents’ occupation (p = .336). These findings suggest that strengthening consistent routines and classroom management may be more impactful than focusing on demographic differences.